Guerrilla warfare and the environment in southern africa: impediments faced by ZIPRA and Umkhonto wesizwe - Chakawa, Joshua; Nyawo-Shava, Vongai Z. (Unisa Press, 2016)
Zimbabwe Peoples’ Revolutionary Army (ZIPRA) was the armed wing of Zimbabwe African People’s Union (ZAPU) which waged the war to liberate Zimbabwe. It operated from its bases in Zambia between 1964 and 1980. Umkhonto Wesizwe (MK) was ANC’s armed wing which sought to liberate South Africa from minority rule. Both forces (MK and ZIPRA) worked side by side until the attainment of independence by Zimbabwe when ANC guerrillas were sent back to Zambia by the new Zimbabwean government. This paper argues that the failure of ZIPRA and Umkhonto Wesizwe to deploy larger numbers of guerrillas to the war front in Zimbabwe (then Rhodesia) and South Africa was mainly caused by bio-physical challenges. ZAPU and ANC guerrillas faced the difficult task of crossing the Zambezi River and then walking through the sparsely vegetated areas, game reserves and parks until they reached villages deep in the country. Rhodesian and South African Defense Forces found it relatively easy to disrupt guerrilla movements along these routes. Even after entering into Rhodesia, ANC guerrillas had environmental challenges in crossing to South Africa. As such, they could not effectively launch protracted rural guerrilla warfare. Studies on ZIPRA and ANC guerrilla warfare have tended to ignore these environmental problems across inhospitable territories. For the ANC, surveillance along Limpopo River and in Kruger National Park acted more as impediments than conduits. ANC also had to cope with almost all challenges which confronted ZIPRA guerrillas such as the Zambezi, Lake Kariba and various parks which Rhodesians always used as a first line of defense but had a geographically difficult task in South Africa where the environment was not attractive for a guerrilla warfare.